2018
DOI: 10.3390/app8050809
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitative Ultrasound Imaging Features of the Abdominal Wall Muscles in Elite and Amateur Basketball Players

Abstract: The aim of the present study was to evaluate and compare with rehabilitative ultrasound imaging (RUSI) abdominal wall muscle thickness and interrecti distance (IRD) between elite and amateur basketball players. A sample of 32 basketball players (age: 23.0 ± 8.5; height: 1.89 ± 14.25 m; weight: 86.6 ± 15.5 kg; body mass index: 22.8 ± 2.6 kg/m 2 ) was divided in two groups: professional elite and amateur players. A diagnostic ultrasound tool with a 7-14 MHz range linear transducer was used for B mode ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
1
16
0
2
Order By: Relevance
“…To the current knowledge, this study may be stated as the first study detailing the abdominal wall muscles and multifidus muscles in patients with chronic mid-portion AT compared with healthy individuals. Our findings were in line with prior research showing a relationship between Achilles Tendinopathy and morphological muscle architecture changes [16][17][18] and regarding the difference of the core muscles between populations [21].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To the current knowledge, this study may be stated as the first study detailing the abdominal wall muscles and multifidus muscles in patients with chronic mid-portion AT compared with healthy individuals. Our findings were in line with prior research showing a relationship between Achilles Tendinopathy and morphological muscle architecture changes [16][17][18] and regarding the difference of the core muscles between populations [21].…”
Section: Discussionsupporting
confidence: 93%
“…Coldron et al [46] reported similar results in postpartum women founding a significantly thinner RA and a wider IRD for the postpartum women. In the same line, Romero et al [21] compared the abdominal wall muscles by USI between elite basketball players and amateur showing a significantly increase for the IRD in favor the elite basketball group with respect group. These results could be related with the high musculoskeletal system demand those who were exposed the elite basketball players due to the multiple training sessions per week.…”
Section: Inter-recti Distance and Rectus Abdominis Thicknessmentioning
confidence: 95%
See 1 more Smart Citation
“…Considering the trunk region, Whittaker et al [21] related the architecture of the abdominal wall muscles with lumbopelvic pain. Several authors argued that USI is a non-invasive, safe and valid method to examine soft tissues and musculoskeletal disorders [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Elite U18 individuals followed a training schedule of 3 hours-per-day, 5 days-per-week and played 1 to 2 matches in a week [17]. In addition, both groups were composed of individuals who have played at least 1 time with the national team [18]. Subjects were excluded if: they underwent a physical therapy treatment, suffered any musculoskeletal injury the last 6 weeks, had skins allergy and any history of lower limb surgery, did not complete all the training sessions, and had other foot orthoses.…”
Section: Participantsmentioning
confidence: 99%